2005
DOI: 10.1111/j.0197-6664.2005.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

The family of origin parachute model: Landing safely in adult romantic relationships*

Abstract: This study investigates the utility of the family of origin parachute model in predicting longitudinal outcomes for couples in romantic relationships. This conceptual model contains common family variables that are theoretically and empirically related to later adult functioning and are believed to influence attitudes that adult children develop regarding romantic relationships as well as self-esteem. Data from two samples were used to analyze this model. The results support the model and demonstrate its abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…First, intergenerational family systems theory (Bowen, 1978) suggests that both the actual level of differentiation in FOO and individuals' perceptions toward their family's differentiating behavior may influence how they develop optimal levels of differentiation of self and, consequently, healthy adult intimate relationships. Second, existing research has shown that not only the FOO experience itself but also how individuals evaluate their FOO experiences are likely to influence the intergenerational transmission process (Busby, Gardner, & Taniguchi, 2005). Thus, our focus was to test the model of intergenerational transmission of relationship quality mediated by individuals' evaluation of the FOO experience.…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…First, intergenerational family systems theory (Bowen, 1978) suggests that both the actual level of differentiation in FOO and individuals' perceptions toward their family's differentiating behavior may influence how they develop optimal levels of differentiation of self and, consequently, healthy adult intimate relationships. Second, existing research has shown that not only the FOO experience itself but also how individuals evaluate their FOO experiences are likely to influence the intergenerational transmission process (Busby, Gardner, & Taniguchi, 2005). Thus, our focus was to test the model of intergenerational transmission of relationship quality mediated by individuals' evaluation of the FOO experience.…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…Martinson suggested that coming to terms meant different things for males and females. Busby, Gardner, and Taniguchi (2005) suggested that family of origin was an important part of research. As such, they encouraged researchers to explore family-of-origin variables when studying adult relationships.…”
Section: Family Of Originmentioning
confidence: 99%
“…It is important, therefore, to consider the multiple contexts that influence a couple and their marital satisfaction (Busby et al 2005). Eco-systems theory suggests a focus on the multiple contexts, while also encouraging a broader, holistic perspective of what contributes to a successful marriage for interracial couples.…”
Section: Strengthening Connections In Interracial Marriagesmentioning
confidence: 99%
“…It also speaks to the multiple environments or levels (micro, mezzo, and macro) that influence the quality of marriage for interracial couples (Leslie and Letiecq 2004). It is important to consider the multiple environments or contexts that influence a couple and their marital satisfaction (Busby et al 2005). Eco-systems theory respects differing experiences of individuals; likewise, research using this perspective speaks to the differing ways men and women experience marital satisfaction (Fiese and Tomcho 2001;Sussman andAlexander 1999, Wilson et al 1997).…”
Section: Utilizing Eco-systems Theory In the Development Of Pre-maritmentioning
confidence: 99%